Vorfahr oder König? - Vidmar, Polona (Acta historiae artis Slovenica, 2021)
The article seeks to shed light on Franz Joseph, Prince of Dietrichstein's interest in the history of his own family, which was reflected among other things in his purchase of the original Dietrichstein family seat in Carinthia in 1838. Franz Joseph's search for the traces of his ancestors in Carinthia and Styria as well as his purchases of objects are analysed based on the prince's not yet published correspondence with the clerks of the seigneuries of Dietrichstein and Gornji Ptuj, which his family inherited from the Counts of Leslie. The article discusses the prince's aspirations to use the inherited, purchased, and commissioned portraits to emphasise the significance of his family and ancestors. As a representative example of the reception of portraits, a series of 14 portraits of European rulers, which Jakob Count of Leslie commissioned for the furnishing of the hall of Ptuj castle between 1669 and 1673 was chosen. Since 1835, seven of the 'sitters' had been recognized in the inventories of the Gornji Ptuj castle as members of the Leslie family, despite the presence of unambiguous props in the paintings, such as crowns, royal orbs and sceptres, and coronation cloaks. The individuals depicted were more accurately identified by the director of the princely gallery Franz Kutschera in 1857, shortly before they were taken to Vienna in 1860, and from there to Frýdlant castle in Bohemia. The paper also highlights the significance of the princely clerks, especially Moritz Seehann and Ferdinand Raisp, for the burgeoning interest in historical and artistic monuments in Ptuj in the 19th century.
Keywords: baročno slikarstvo; baroque painting; Count of Leslie, Jakob; grof Leslie, Jakob; Habsburg (rodbina); knez Dietrichstein, Franc Jožef; naročništvo; patronage; portraits; portreti; Prince of Dietrichstein, Franz Joseeph; Ptuj Castle; ptujski grad; Reisp, Ferdinand; transfer of atrwork; transfer umetnin